Imagined Worlds and Classroom Realities: Mythopoetic Provocations for Teachers and Teacher Educators - Shann, Steve (Springer, 2016)
"Stories matter. Stories speak about complex aspects of our lives that intuitively we know are important but for which the language of rational discourse is often inadequate. Stories draw on archetypal structures and evocative language in ways that create affect: they penetrate, provoke, and disturb. This is a book of nine stories about teachers and students. A young woman sits in her first teacher-education lecture and wonders what kind of a tribe she is joining. A preservice teacher clashes with his mentor teacher on a practicum. A teacher and students inhabit an online space with unpredictable consequences. Sally discovers the Universarium. Joseph writes a story that undoes his therapist. Sylvia struggles to free herself from an oppressive discourse about the nature of teaching. Two siblings support and console each other through their complex inductions into classroom lifeworlds. A secondary student goes missing and police, the media and his teachers wonder why. A teacher-education academic wrestles with elusive ideas in order to prepare a lecture that he hopes will make a more-than-passing impact. There is no other book like Imagined Worlds and Classroom Realities. It not only tells nine gripping stories, but also positions these stories as part of a growing scholarship about story-telling. It includes, as well, practical ways of using the stories in teacher education and professional development. Steve Shann is a teacher and writer with over forty years experience in primary, secondary and tertiary classrooms. "